2018
DOI: 10.1001/jamainternmed.2018.2413
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Long-term Benzodiazepine Use Among Older Adults

Abstract: Benzodiazepine use among older adults is common despite evidence for many potential risks. While treatment guidelines recommend short-term use of benzodiazepines, up to one-third of use is long term, which is most common among older adults. 1 To reduce benzodiazepine prescribing to older adults, one potential point for intervention is at the transition from new to long-term use, yet little is known about the factors that predict conversion to long-term use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 6 publications
(16 reference statements)
1
26
0
Order By: Relevance
“…Several studies have found a positive correlation between BZD use and fall-related incidents among older adults. BZDs are psychoactive drugs with therapeutic eff ects (e.g., antianxiety, anti-epileptic, muscle relaxant) (Díaz-Gutiérrez et al, 2017), but are commonly prescribed to treat insomnia, anxiety, and agitation (odds ratio [OR] = 4.05; 95% confi dence interval [CI] [4.44,11.43]) in older adults (Gerlach, Maust, Leong, Mavandadi, & Oslin, 2018). A systematic review involving 18 studies from various countries by Yu and Zecevic (2018) on recurrent or two or more falls over 12 months in older adults living in the community reported an increased risk of 1.2 to 3.7 times in older adults taking BZDs.…”
Section: Benzodiazepine Use and Fall-related Incidentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have found a positive correlation between BZD use and fall-related incidents among older adults. BZDs are psychoactive drugs with therapeutic eff ects (e.g., antianxiety, anti-epileptic, muscle relaxant) (Díaz-Gutiérrez et al, 2017), but are commonly prescribed to treat insomnia, anxiety, and agitation (odds ratio [OR] = 4.05; 95% confi dence interval [CI] [4.44,11.43]) in older adults (Gerlach, Maust, Leong, Mavandadi, & Oslin, 2018). A systematic review involving 18 studies from various countries by Yu and Zecevic (2018) on recurrent or two or more falls over 12 months in older adults living in the community reported an increased risk of 1.2 to 3.7 times in older adults taking BZDs.…”
Section: Benzodiazepine Use and Fall-related Incidentsmentioning
confidence: 99%
“…Findings also included overdosage, underdiagnosis, and guidelines not being followed. Treating sleep problems with BZDs is a common misuse among older adults because of their short-term eff ectivity (Canady, 2018) and resulting low quality of sleep (Gerlach et al, 2018). In addition, BZD use increases in prevalence with age.…”
Section: Benzodiazepine Use and Fall-related Incidentsmentioning
confidence: 99%
“…benzodiazepines, is a class of drugs for which not only the misuse of prescription guidelines is implicated, but also a vicious circle in which an unsuccessful shared decision process and health advocacy intervenes (renew of prescriptions on the basis of a postulated patient dependence, lack of offer of alternative therapies for the treatment of insomnia, failure to educate patients about the risks of the medication). 34 In accordance with the principles of the "Choosing Wisely" campaign, our goal was also the improvement of the Moreover, our study highlighted the important effect of the peer-to-peer comparison on prescription habits.…”
Section: Discussionmentioning
confidence: 54%
“…First, the medication to which the intervention was directed; benzodiazepines, is a class of drugs for which not only the misuse of prescription guidelines is implicated, but also a vicious circle in which an unsuccessful shared decision process and health advocacy intervenes (renew of prescriptions on the basis of a postulated patient dependence, lack of offer of alternative therapies for the treatment of insomnia, failure to educate patients about the risks of the medication) …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the over-riding determinant for benzodiazepine use is its previous use. In a recent study of a sample of the senior citizen, Gerlach et al found that nearly one-third of patients went on to long-term use 27. Some users may have a genetic predisposition to opioid dependence.…”
Section: Discussionmentioning
confidence: 99%